URGENSI PEMAHAMAN JENIS KELAMIN DAN GENDER PADA ANAK USIA DINI: THE URGENCY OF UNDERSTANDING SEX AND GENDER IN EARLY CHILDHOOD - Jannah, Shofiatul; Bramastia, Lutfia Sefta (Universitas Islam Malang, 2021)
Early childhood is aged 0-8 years, early childhood aged 4-6 years get formal education called early childhood education in Kindergarten / Raudhatul Athfal, this education has a function to provide a stimulus to early childhood so that Aspects of development and basic potential possessed by children develop so that they can become the initial fundamentals of children so that they can continue their further education. Educators play an important role in educational education about gender and gender in early childhood by adjusting the characteristics of early childhood. So that children at an early age can distinguish their roles and do not deviate from behavior according to their nature. This type of research is a qualitative research. There are 4 methods used, namely, habituation, storytelling, conversing and sociodrama. The media used is image media. The changing learning behavior of children includes children who are able to classify themselves and children understand how to look the right way as a boy and a girl. The results showed that the introduction of gender and gender is very important in learning so that children understand their responsibilities according to their roles and do not engage in deviant behavior.